Efficacy and Safety of Daprodustat Vs rhEPO for Anemia in Patients With Chronic Kidney Disease: A Meta-Analysis and Trial Sequential Analysis - Zhangning Fu; Zhangning Fu; Xiaodong Geng; Xiaodong Geng; Kun Chi; Kun Chi; Chengcheng Song; Chengcheng Song; Di Wu; Chao Liu; Chao Liu; Quan Hong; et al. (Frontiers Media S.A., 2022)
Introduction: Daprodustat, a novel hypoxia-inducible factor prolyl-hydroxylase inhibitor (HIF-PHI), its efficacy and safety remain unclear. Thus, we conducted this meta-analysis aiming at investigating its efficacy and safety on the treatment of patients with chronic kidney disease (CKD)-related anemia.Methods: We systematically searched for relevant studies in PubMed, Embase, Cochrane Library and Clinical Trial Registries databases from inception until December 2021. We selected randomized controlled trials comparing daprodustat with recombinant human erythropoietin (rhEPO) in anemia patients with CKD with or without dialysis.Results: Seven studies including 7933 patients met the inclusion criteria. For both nondialysis-dependent (NDD-) CKD and dialysis-dependent (DD-) CKD patients, the pooled results showed that there was no significant difference in the changes in hemoglobin levels between the daprodustat and rhEPO groups (mean difference (MD) = −0.01, 95% confidence interval (CI) = −0.38, 0.35, p = 0.95; MD = 0.15, 95% CI = −0.29, 0.60, p = 0.50; respectively). In addition, a significant increase in transferrin saturation (TSAT), total iron binding capacity (TIBC) and total iron was observed in daprodustat groups compared with rhEPO groups in DD-CKD patients (p < 0.05). As for safety, the overall frequency of adverse events was similar between the daprodustat and rhEPO groups in DD-CKD patients (relative risk (RR) = 0.99, 95%CI = 0.92, 1.06, p = 0.76), and the trial sequential analysis (TSA) confirmed this result. But for NDD-CKD patients, the incidence of adverse events in the daprodustat groups was significantly higher than that of rhEPO groups (RR = 1.04, 95%CI = 1.01,1.07, p = 0.02), while the TSA corrected this result. No trend of increasing incidence of serious adverse events was found in all daprodustat treated patients, but the TSA could not confirm this result.Conclusion: Although daprodustat was noninferior to rhEPO in correcting anemia in both NDD-CKD and DD-CKD patients, it seemed to have a better effect on optimizing iron metabolism in DD-CKD patients. Daprodustat may be a promising alternative for the treatment of anemia in patients with CKD. However, due to the lack of included studies, future researches are needed to further evaluate the therapeutic effect of daprodustat.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier CRD42021229636.